PENGARUH LATAR BELAKANG PENDIDIKAN AGAMA DAN SEMANGAT WIRAUSAHA TERHADAP KINERJA BISNIS MAHASISWI MUSLIMAH ENTERPREUNER DI KOTA BANDUNG - Diden Rosenda (GoAcademica Research dan Publishing, 2021)
The purpose of this study was to determine the effect of religious education background, and entrepreneurial spirit on the business performance of Muslim female entrepreneurs in Bandung. This research uses qualitative research with descriptive analysis approach. The data in the study consisted of primary data and secondary data. Methods of collecting data using interview methods and literature study. The research respondents were 45 business students from various universities in the city of Bandung. Research respondents used the purposive sampling method. Students who have a religious education background in Islamic boarding schools get the highest score in relation to improving business performance, This is because in Islamic boarding schools respondents are taught the character of an entrepreneur who is independent, honest, disciplined, hardworking, not easy to give up and innovative. Students who have the spirit of worship in running their business get the highest score in relation to business performance.